2022
DOI: 10.1051/0004-6361/202244197
|View full text |Cite
|
Sign up to set email alerts
|

Data on 824 fireballs observed by the digital cameras of the European Fireball Network in 2017–2018

Abstract: Meteoroids impacting the Earth on a daily basis are fragments of asteroids and comets. By studying fireballs produced during their disintegration in the atmosphere, we can gain information about their source regions and the properties of their parent bodies. In this work, data on 824 fireballs presented in an accompanying paper and catalog are used. We propose a new empirical parameter for the classification of the physical properties of meteoroids, based on the maximum dynamic pressure suffered by the meteoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The trend in PE values depending on the mass of meteoroids is also very clear, that is, more massive meteoroids are more fragile. The PE criterion for 3 Draconid and other fireballs observed in 2017-2018 (Borovička et al 2022a) shows that the τ Herculids we observed are the most fragile meteoroids observed ever. Their PE is usually lower than Hurbanovo (all-sky+IP), Kunžak (all-sky+IP), Rimavská Sobota (all-sky), Martinsberg (all-sky), Veselí nad Moravou (IP), Ondřejov (IP) that of other meteors and even than that of Draconid meteors of the same mass.…”
Section: En310522_013924: the Exceptional Case Of A Bright τ Herculid...mentioning
confidence: 55%
“…The trend in PE values depending on the mass of meteoroids is also very clear, that is, more massive meteoroids are more fragile. The PE criterion for 3 Draconid and other fireballs observed in 2017-2018 (Borovička et al 2022a) shows that the τ Herculids we observed are the most fragile meteoroids observed ever. Their PE is usually lower than Hurbanovo (all-sky+IP), Kunžak (all-sky+IP), Rimavská Sobota (all-sky), Martinsberg (all-sky), Veselí nad Moravou (IP), Ondřejov (IP) that of other meteors and even than that of Draconid meteors of the same mass.…”
Section: En310522_013924: the Exceptional Case Of A Bright τ Herculid...mentioning
confidence: 55%
“…The distribution of aerodynamic pressure that fragments asteroidal fireballs varies more than in Geminids because the fireballs are a random sample of sporadic background. Additionally, the fireballs used for the modeling were chosen to be similar to Geminids in terms of entry masses and some also in velocities, masses and velocities that are less typical for asteroidal orbits (Borovička et al 2022a). Therefore, we could have expected the modeled meteoroids would come from various sources and would have different mechanical properties as well.…”
Section: Discussionmentioning
confidence: 99%
“…The unclear formation scenario and the actual nature of Phaethon and the Geminids is the main motivation for the present study. Another motivation is the notion that small Geminids tend to be weaker than large ones (Borovička et al 2022a). Therefore, we address the question of the physical and mechanical properties of the Geminid meteoroid material by modeling their fragmentation cascade in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may not be convincing enough in the case of 2022 EB5, since the terminal height where the bright trajectory ends remains unknown and the calculation of terminal height can be very dependent on the fragmentation model chosen. A newly defined parameter, called the pressure resistance factor or pressure factor (PF) was proposed by Borovicka et al (2022) to evaluate the structural strength on the basis of the maximal ram pressure. We chose the PF parameter to constrain the material strength of the object as the maximum ram pressure is more robust, easier to obtain and less dependent on observing circumstances than the terminal height.…”
Section: Physical Properties Of 2022 Eb5mentioning
confidence: 99%